2011
DOI: 10.1177/0961203310392427
|View full text |Cite
|
Sign up to set email alerts
|

Acute lumbosacral polyradiculoneuropathy heralding transformation to systemic lupus erythematosus in a patient with discoid lupus

Abstract: Systemic lupus erythematosus (SLE) is a multisystemic autoimmune disease with which a variety of neuropathic disorders have been associated. Among these, the acute inflammatory demyelinating polyradiculoneuropathy variant of Guillain-Barré syndrome has been well established. However, acute axonal lumbosacral polyradiculoneuropathy accompanied by albuminocytological dissociation in the cerebrospinal fluid has been extremely rarely reported in SLE. We report on a 47-year-old woman with discoid lupus presenting w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Most cases had demyelinating variant. The seven cases of axonal variant from previous reports [13][14][15][16][17][18] and our case are summarized in Table 2. Most of the cases of GBS occurred in the early course of SLE and were treated with a variety of immunotherapy regimens.…”
Section: Discussionmentioning
confidence: 94%
“…Most cases had demyelinating variant. The seven cases of axonal variant from previous reports [13][14][15][16][17][18] and our case are summarized in Table 2. Most of the cases of GBS occurred in the early course of SLE and were treated with a variety of immunotherapy regimens.…”
Section: Discussionmentioning
confidence: 94%
“…However, in the follow-up study, the motor nerves showed only mild improvements in amplitude on the upper limbs, and unobtainable distal compound muscle action potential findings on the lower limbs suggested that axonal degeneration was more likely to occur than distal conduction block. In severe cases, surviving patients with concomitant AMAN and SLE could experience substantial functional loss because of impaired motor function despite the medical treatment 8 . Acute motor axonal neuropathy is associated with a higher severity of disability assessed using the GBS disability scale than the demyelinating subtype 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Only a few previous studies have reported frequent occurrence of NP in SLE, with incidences from 1.5% to 27.8% [ 2-7 ]. NP usually develops during the course of the SLE, especially in the advanced stage of the SLE, and very rarely from the outset of the SLE [ 8 , 9 ]. AIDP is the most prevalent form of GBS.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of SLE in AIDP or GBS has been reported to be 0.6-1.7% [ 2 , 10 ]. Our review of the literature finds that AIDP or GBS with SLE was more common in females (73.3%, 11/15) than males (26.7%, 4/15), and cerebrospinal fluid albuminocytological dissociation was present in 66.7 % (9/15) of cases, and more importantly, usually occurred in early course of the SLE ( Table 2 ) [ 8 , 9 , 11-23 ], even as the first manifestation of SLE [ 8 , 16-21 ]. We reported the AIDP patient with SLE occurring early in the course of lupus, which was consistent with the previously reported ones [ 16 ].…”
Section: Discussionmentioning
confidence: 99%